2022
DOI: 10.1007/s00031-022-09756-2
|View full text |Cite
|
Sign up to set email alerts
|

Covering Numbers of Unipotent Conjugacy Classes in Simple Algebraic Groups

Abstract: For simple algebraic groups defined over algebraically closed fields of good characteristic, we give upper bounds on the covering numbers of unipotent conjugacy classes in terms of their (co)ranks and in terms of their dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Continuing with the discussion of the case where G is a finite simple group and C a nontrivial conjugacy class, the main result of [19] shows that there is an absolute constant c such that cn(G, C) ≤ c log |G| log |C| for all such G, C. (Obviously log |G| log |C| is a lower bound for the covering number.) In [22], it is suggested that an analogous result should hold for algebraic groups: namely, there should be a constant c such that cn(G, C) ≤ c dim G dim C for all non-central conjugacy classes C of simple algebraic groups G. Such a bound is established in [22, Theorem C] for the case where C is a unipotent conjugacy class in good characteristic. In this paper we prove such a result in general.…”
Section: Introductionmentioning
confidence: 99%
“…Continuing with the discussion of the case where G is a finite simple group and C a nontrivial conjugacy class, the main result of [19] shows that there is an absolute constant c such that cn(G, C) ≤ c log |G| log |C| for all such G, C. (Obviously log |G| log |C| is a lower bound for the covering number.) In [22], it is suggested that an analogous result should hold for algebraic groups: namely, there should be a constant c such that cn(G, C) ≤ c dim G dim C for all non-central conjugacy classes C of simple algebraic groups G. Such a bound is established in [22, Theorem C] for the case where C is a unipotent conjugacy class in good characteristic. In this paper we prove such a result in general.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, if G is a Chevalley group defined over an algebraically closed field, they show that ecn(G) ≤ 4 • rk(G). Extending [17,Theorem 1.1], upper bounds on covering numbers of unipotent conjugacy classes are given in terms of their dimension and in terms of their (co)ranks in [25] for G a simple algebraic group over an algebraically closed field k of good characteristic. Recall that the characteristic p of k is good for G if p = 2 when G is not of type A, p = 3 if G is an exceptional group and p = 5 if G is of type E 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Recall that the characteristic p of k is good for G if p = 2 when G is not of type A, p = 3 if G is an exceptional group and p = 5 if G is of type E 8 . Theorem C in [25] is extended and improved by [18, Theorem 1] where it is shown that there exists an absolute constant c ≤ 120 such that whenever C is a non-central conjugacy class of a simple algebraic group G then C k = G for any integer k at least c • (dim(G)/ dim(C)).…”
Section: Introductionmentioning
confidence: 99%